Path to prosperity : Hamilton Project ideas on income security, education, and taxes - Furman, Jason; Bordoff, Jason (Brookings Institution Press, 2008)
"Focuses on three key criteria for fostering broadly shared economic growth: enhancing economic security, building a highly skilled work force, and reforming the tax system. Proposals include reforming unemployment insurance, improving incentives for retirement saving, building quality into each level of education, and simplifying taxation and making it more progressive"--Provided by publisher